A global and some national perspectives on the current evidence of interventions on fruit and vegetable intake in low-, middle-, and high-income countries - Hess, Sonja Y.; Angeles-Agdeppa, Imelda; Kinabo, Joyce; Mitchodigni, Irene Medeme; Silva, Renuka; Tharaney, Manisha; Azupogo, Fusta; Bliznashka, Lilia; Hinnouho, Guy-Marino; Koyratty, Nadia; Smith, Taryn J.; Olney, Deanna K. (SAGE Publications, 2025)
Adequate amounts of fruit and vegetables (F&V) are an important part of a healthy diet, yet intake is suboptimal in most population groups worldwide. To better understand the evidence of strategies aiming to improve F&V intake, we conducted a scoping review of interventions assessing the impact on F&V intake, including those aiming to improve F&V intake explicitly and those targeting diet, health, lifestyle, or food environment generally. Among all eligible interventions reviewed, most of which were implemented in high-income countries, about half reported a significant positive impact on fruit and/or vegetable intake. Interventions that used a multicomponent strategy (61%) and those that focused on F&V specifically (72%) were most likely to find a significant increase in fruit and/or vegetable intake. Detailed summaries are provided in 2 accompanying articles. In the present article, we put these findings into perspective. Specifically, we considered the evidence for 4 target countries of the Fruit and Vegetables for Sustainable Healthy Diets Initiative: Benin, the Philippines, Sri Lanka, and Tanzania. When considering available evidence at the national level, there is a paucity of information from intervention trials despite evidence of inadequate F&V intakes in each of these countries. When considering available evidence at the global level, and especially for low-and-middle income countries, there is a critical need to strengthen the evidence across various intervention strategies, particularly related to targeting, timing, intensity, duration, frequency, and other key characteristics, to better understand how to enhance their impact on F&V intake in various population groups and contexts.